Impaired macrophage phagocytosis in non‐eosinophilic asthma. Issue 1 (24th December 2012) - Simpson, J. L.; Gibson, P. G.; Yang, I. A.; Upham, J.; James, A.; Reynolds, P. N.; Hodge, S.; ,
Summary Background Many patients with non‐eosinophilic asthma have increased numbers of neutrophils in the airways. The explanation for this chronic inflammation remains unclear, but may result from an impaired ability of alveolar macrophages to phagocytose apoptotic cells (a process termed 'efferocytosis'), as we have shown in chronic obstructive pulmonary disease (COPD). Objectives To examine induced sputum as a non‐invasive technique to characterize efferocytosis in chronic lung diseases and to compare efferocytosis in patients with non‐eosinophilic asthma, eosinophilic asthma and COPD. Methods Participants with stable asthma (20 with eosinophilic and 30 with non‐eosinophilic) and COPD (n = 11) underwent clinical assessment including allergy skin tests, saline challenge and sputum induction. Sputum cells were dispersed using dithiothreitol and resuspended in culture medium. Efferocytosis of apoptotic bronchial epithelial cells by sputum‐derived macrophages was determined using flow cytometry. Results There were no significant differences in efferocytosis between paired sputum and bronchoalveolar lavage macrophages from three subjects. Efferocytosis was significantly impaired in patients with non‐eosinophilic asthma [mean (SD) 0.95 (0.24)] compared with eosinophilic asthma [1.17 (0.19)] and to a similar degree as patients with COPD [1.04 (0.16)]. Sputum neutrophils were significantly higher in patients with COPD and non‐eosinophilic asthma compared with eosinophilic asthma. Conclusion and Clinical Relevance Induced sputum provides a reliable and non‐invasive method for studying macrophage efferocytosis in chronic lung disease. Macrophage efferocytosis is impaired in non‐eosinophilic asthma to a similar degree as that in COPD and may explain the persistent airway neutrophilia and chronic inflammation that characterizes this asthma subtype.